Investigations of the compressive mechanical properties of open-cell hollow-sphere structures. (September 2020) - Dai, Meiling; Jiang, Hanyang; Dai, Xiangjun; Chen, Gongfa; Yang, Fujun; He, Xiaoyuan
Highlights: Compressive mechanical properties of the open-cell hollow-sphere structures were studied experimentally and numerically. The geometric models of the open-cell hollow-sphere structures, in which the connecting regions are perforated through, were derived from the traditional soldered or adhesive bonded MHSS. Numerical studies confirmed the significant influence of the perforations between spheres on the mechanical properties of hollow-sphere structures. The base material parameters also have certain influences on the mechanical properties of the structures. The negative poisson's ratio effect of such hollow-sphere structures in BCC and FCC packing patterns has also been found. Abstract: The compressive mechanical properties of open-cell hollow-sphere structures were experimentally and numerically investigated. The geometric model of the structure, through which the connected regions between spheres were perforated, was derived from the traditional metallic hollow-sphere structure (MHSS). For the experimental study, 3D printing technology was used to fabricate structures made of nylon in different arrangements, such as simple cubic (SC), body-centred cubic (BCC) and face-centred cubic (FCC). The experimental results validated the effectiveness of the finite element models for structures arranged in different packing patterns. Based on numerical simulations, parametric studies were conducted to investigate the influences of the geometrical and material parameters on the basic mechanical properties of the structure, including the elastic modulus, Poisson's ratio and initial yield stress. The results confirmed the significant impact of the structure's relative densities, which depend on the different geometrical parameters, such as the spheres' spatial pattern, wall thickness and connection radius, on the mechanical properties of the structure. Additionally, the influence of the material parameters, such as Young's modulus and the yield stress, on the mechanical properties were also detected and validated.